Infrastructure for the practice of sports in São Paulo post – FIFA World Cup Brazil 2014 (Fiep Bulletin - online, 2017)
The sports mega events can be an opportunity for the development of the sport in the host cities. However it has to beplanned legacies and impacts in advance to mega events. So, the objectives of the study were identify the sports public policy ofthe Municipal Secretary of Sport, Leisure and Recreation of the city of São Paulo (SEME), during the administrations of mayorsKassab (2009-2012) and Haddad (2013-2016) and analyze the promotion in infrastructure for sports practices before and afterthe completion of the mega events in Brazil, evaluating the possible legacies of the mega event – FIFA Brazil World Cup 2014.The research methodology consisted in the documental analysis and qualitative interview with nine employees of SEME. It wasnoted a decrease in the promotion of the sport in the city, with the reduction of resources and poor infrastructure and inadequateto population and misguided investments in sports events. To analyze the two managements it can be realized that the sportlanguishing in São Paulo, already for some time, and the FIFA World Cup-Brazil 2014, that could be a boost to the recovery, didnot change the picture. Proving that the mega events have many promises of development, but, are not accomplished.